2019
DOI: 10.1186/s12889-019-6533-7
|View full text |Cite
|
Sign up to set email alerts
|

Area-level deprivation and preterm birth: results from a national, commercially-insured population

Abstract: Background: Area-level deprivation is associated with multiple adverse birth outcomes. Few studies have examined the mediating pathways through which area-level deprivation affects these outcomes. The objective of this study was to investigate the association between area-level deprivation and preterm birth, and examine the mediating effects of maternal medical, behavioural, and psychosocial factors. Methods: We conducted a retrospective cohort study using national, commercial health insurance claims data from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 40 publications
5
37
0
Order By: Relevance
“…For example, neighbourhood deprivation is associated with incidence of preterm birth. 11,12 In children, socioeconomic deprivation assessed at a household level or using area-based socioeconomic indexes correlates with childhood mortality. 13 Less is known about the associations of SES on health outcomes in preterm infants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, neighbourhood deprivation is associated with incidence of preterm birth. 11,12 In children, socioeconomic deprivation assessed at a household level or using area-based socioeconomic indexes correlates with childhood mortality. 13 Less is known about the associations of SES on health outcomes in preterm infants.…”
Section: Discussionmentioning
confidence: 99%
“…Socioeconomic factors have been associated with worse health outcomes in adult and paediatric populations. For example, neighbourhood deprivation is associated with incidence of preterm birth . In children, socioeconomic deprivation assessed at a household level or using area‐based socioeconomic indexes correlates with childhood mortality .…”
Section: Commentmentioning
confidence: 99%
“…It is well known that area-level socioeconomic conditions have a contextual association with an individual's health outcomes [1][2][3]. Many studies have indicated that area-level deprivation, which re ects various aspects of an area's socioeconomic positions, can affect the health outcomes of its residents, including mortality [4][5][6][7], morbidity [8][9][10][11], mental health [12,13], poor birth outcomes [14][15][16], and health risk behavior [17,18]. The impact of area-level deprivation on health matters for not only public health policies but also macroeconomic and social policies, which are committed to income redistribution, labor market regulations, and other issues related to social welfare.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the association between area-level deprivation and health, two issues have remained to be addressed. First, the impact on self-rated health (SRH), which represents overall health conditions [27,28], or subjective well-being (SWB), which is often expressed by life satisfaction (LS) [29,30], has been relatively understudied, compared to the impact of area-level deprivation on mortality, morbidity, or other speci c health outcomes [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Meanwhile, many studies have examined the association between arealevel income inequality or poverty and an individual's SRH or SWB [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation